2022
DOI: 10.1007/s13721-021-00341-3
|View full text |Cite
|
Sign up to set email alerts
|

Screening of potential inhibitors of COVID-19 with repurposing approach via molecular docking

Abstract: is the causative organism for a pandemic disease with a high rate of infectivity and mortality. In this study, we aimed to assess the affinity between several available small molecule and proteins, including Abl kinase inhibitors, Janus kinase inhibitor, dipeptidyl peptidase 4 inhibitors, RNA-dependent RNA polymerase inhibitors, and Papainlike protease inhibitors, using binding simulation, to test whether they may be effective in inhibiting COVID-19 infection through several mechanisms. The efficiency of inhib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…The protein is comprised of several domains, including the N-terminal domain (1-397), finger domain (397-581 and 629-687), the palm region (582-628 and 688-815) and the thumb region (816-596) (27). The docking analysis revealed that christanoate has a higher affinity towards the active residues, which is similar to Remdesivir reported by Alizadehmohajer et al, (26) involving Lys47, His133, Asp135, Ala706, Ser709, Thr710, Gly774, Lys780 and Ser784 via hydrophobic contact in christanoate. Their study mentioned that the residues interacted with would establish an environment cohesive and stable upon forming the complex.…”
Section: Christanoate Chain A: Asn138supporting
confidence: 80%
See 1 more Smart Citation
“…The protein is comprised of several domains, including the N-terminal domain (1-397), finger domain (397-581 and 629-687), the palm region (582-628 and 688-815) and the thumb region (816-596) (27). The docking analysis revealed that christanoate has a higher affinity towards the active residues, which is similar to Remdesivir reported by Alizadehmohajer et al, (26) involving Lys47, His133, Asp135, Ala706, Ser709, Thr710, Gly774, Lys780 and Ser784 via hydrophobic contact in christanoate. Their study mentioned that the residues interacted with would establish an environment cohesive and stable upon forming the complex.…”
Section: Christanoate Chain A: Asn138supporting
confidence: 80%
“…The primary protein catalyzes the viral RNA replication and transcription process. Therefore, inhibiting this enzyme will suppress viral replication and further infection (26). The protein is comprised of several domains, including the N-terminal domain (1-397), finger domain (397-581 and 629-687), the palm region (582-628 and 688-815) and the thumb region (816-596) (27).…”
Section: Christanoate Chain A: Asn138mentioning
confidence: 99%
“…Another pyrrolopyrimidine analog, abivertinib, was found to depress cytokine production in patients with COVID-19. 323 Several pyrimidine analogs have also been found to combat SARS-CoV-2. For example, according to a recent study conducted by Huntington et al, GLPG-0187, which bears a pyrimidin ring, effectively blocked SARS-CoV-2 pseudovirus infection across multiple viral variants, especially the Omicron and Delta pseudovirus variants, in a dose-dependent manner.…”
Section: Structures Of Small Molecule Drugs For Covid-19 Therapymentioning
confidence: 99%
“…This process involves the prediction of ligand conformation and orientation within a specific binding site, involving algorithms and scoring functions that allow predicting biological activity by evaluating interactions between compounds and potential targets [91]. Both Autodock4 and its graphical interface, AutoDockTools, are available as free and open source software for Microsoft Windows, Mac OS, and Linux systems, Although there is ample evidence of the use of Autodock4 in the search for and development of potential drugs against Cancer, HIV, and COVID-19, among other diseases [92][93][94][95][96][97], its use has also been reported in the training of students in areas related to medicine, bioinformatics, and education [10,[98][99][100].…”
Section: Computational Chemistry Elementsmentioning
confidence: 99%